1999
DOI: 10.1259/bjr.72.860.10624337
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of proximal femur in the prediction of hip fracture in osteoporotic women.

Abstract: 111 White post-menopausal women with hip fracture and 329 healthy controls were studied in order to determine whether proximal femur geometry predicts hip fracture and improves the discriminant ability of femoral neck bone mineral density (BMD) in elderly women. All subjects underwent dual X-ray photon absorptiometry (DXA) of the hip from which the femoral neck BMD, hip axis length, femoral neck width and femoral neck-shaft angle were measured. Fractured subjects had a lower femoral neck BMD, a longer hip axis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
90
5
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 32 publications
11
90
5
4
Order By: Relevance
“…Nevertheless, it should be pointed out that in males, a statistically significant inverse relationship between the NSA and FN-BMD was found, as already reported by others, 14,18 which was not observed in females. 26,29 The latter finding was also reported by other authors, 9,30 who found NSA to be an independent predictor of hip fracture in females. Therefore, it may be that the negative correlation of FN-BMD with NSA leads BMD to capture some of the effects of NSA on hip fracture; thus explaining, at least partially, the disagreement between males and females regarding the independence of the ability of NSA to predict hip fracture.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Nevertheless, it should be pointed out that in males, a statistically significant inverse relationship between the NSA and FN-BMD was found, as already reported by others, 14,18 which was not observed in females. 26,29 The latter finding was also reported by other authors, 9,30 who found NSA to be an independent predictor of hip fracture in females. Therefore, it may be that the negative correlation of FN-BMD with NSA leads BMD to capture some of the effects of NSA on hip fracture; thus explaining, at least partially, the disagreement between males and females regarding the independence of the ability of NSA to predict hip fracture.…”
Section: Discussionsupporting
confidence: 80%
“…This agrees with reports by some authors 16,18 but is in contrast to the findings of Alonso et al 14 and the majority of reports in the literature about NSA hip fracture prediction in females. 10,11,14,22,26 Concerning the independence of the ability of NSA to predict hip fracture, the contrasting results between previous studies in females 10,29 and the present one in males might be a result of a statistical weakness of the present study because of the low number of fractures in males. Nevertheless, it should be pointed out that in males, a statistically significant inverse relationship between the NSA and FN-BMD was found, as already reported by others, 14,18 which was not observed in females.…”
Section: Discussioncontrasting
confidence: 66%
“…Recent data suggest that weakened cortical bone may primarily be responsible for hip intracapsular hip fracture (6), thus emphasizing the importance for quantitatively assessing and monitoring cortical structure. Support for the role of cortical bone architecture as a risk factor for hip fracture is found in several studies of postmenpausal osteoporosis, where strong associations have been reported between proximal femur geometry and fracture incidence (7)(8)(9). Additionally, bone mineral density (BMD) supplemented by femoral geometry has been shown to be more predictive of breaking strength than BMD alone (10).…”
Section: Introductionmentioning
confidence: 99%
“…However, the two density distributions, of patients at-risk and age-matched controls, have been found to overlap by large amounts, reducing the accuracy of classification to about 65% [2]. It has been shown that, in addition to BMD, other structural parameters, such as bone architecture and bone geometry, also play a nonnegligible role in determining bone competence [3][4][5][6][7][8].…”
mentioning
confidence: 99%